Lost in space / Suzana Ab. Rahim - Ab. Rahim, Suzana (Academy of Language Studies, 2022)
Blue is the colour of the sky We stare straight up above Adorned with all sorts of billowing sizes and shapes White and off-white spread across Dancing, Clouding our very eyes